Current Trends in Ancient Grains‐Based Foodstuffs: Insights into Nutritional Aspects and Technological Applications. Issue 1 (7th November 2017) - Boukid, Fatma; Folloni, Silvia; Sforza, Stefano; Vittadini, Elena; Prandi, Barbara
Abstract: For centuries, ancient grains fed populations, but due to their low yield, they were abandoned and replaced by high‐yielding species. However, currently, there is a renewed interest in ancient wheat and pseudocereal grains from consumers, farmers, and manufacturers. Ancient wheat such as einkorn, emmer, spelt, and Kamut®, are being reintegrated because of their low fertilizer input, high adaptability and important genetic diversity. New trends in pseudocereal products are also emerging, and they are mostly appreciated for their nutritional outcomes, particularly by the gluten‐free market. Toward healthier lifestyle, ancient grains‐based foodstuffs are a growing business and their industrialization is taking 2 pathways, either as a raw ingredient or a functional ingredient. This paper deals with these grain characteristics by focusing on the compositional profile and the technological potential.